105 Actually, it is easy being green: Ten years of the Canadian PAediatric Society Annual General Meeting viewed through a sustainability lens. (19th August 2020) - Hicks, Alex; Hicks, Anne
Abstract: Introduction/Background: The Canadian Paediatric Society (CPS) recently released the "Global climate change and health of Canadian Children" statement. As climate rapidly evolves from "change" to "crisis" there is an increasing pressure toward sustainable conferencing. Knowing the value of attending meetings, the growing body of literature evaluating travel-related carbon cost and convention sustainability can inform environmental harm minimization. Conferences can pressure venues to increase sustainability by choosing sites and venues wisely and communicating their requirements to rejected venues. They can also offer carbon offset purchase through credible companies (e.g. Gold Standard). Over the last 10 years the CPS has conducted its Annual General Meeting (AGM) at host cities that reflect Canada's large geographic footprint. Venues included both hotel and standalone conference centers. There is no published evaluation of sustainable practices for CPS meetings. Objectives: Evaluate the past 10 CPS Annual General Meetings (AGMs) for: The round trip carbon cost of travel from pediatric residency program training sites Host city ground transportation options Venue supports and policies promoting sustainable conferences and communities Design/Methods: Travel-related carbon cost was estimated with a round-trip calculator for economy seating the most direct available flights (https://co2.myclimate.org/en/offset_further_emissions ). Cities of origin for attendee were the 11 CaRMS-matched pediatric residency training programs (https://www.carms.ca/match/psm/program-descriptions/ ). Venues were evaluated based on current publicly available self-reported information using conference sustainability criteria suggested through a literature review and public rating tools (Green Key, Quality Standards of the International Association of Convention Centres). Ground transportation from the airport was scored /3 by: public transport from airport (1), formal shared transport (1), fee deterrence for parking (1). Venue type was split by hotel-associated (H) and standalone convention centre (CC) meeting facilities. Sustainability of meeting facilities was divided into supports /2 (rentable supports, links to local vendors, catering and personnel) for exhibitors (1) and event planners (1), policies /3 by: sustainability, promotion of a green community (1), and waste management (1), and walkability from accommodation /1. Results: The last 10 CPS AGMs were held in western (3; Vancouver 2010, Edmonton 2013, Vancouver 2017), eastern (1; Charlottetown 2016) and central (6; Quebec City 2011, London 2012, Montreal 2014, Toronto 2015, Quebec City 2018, Toronto 2019) provinces; in 2020 it is in Vancouver. Central Canada sites had the lowest air travel carbon cost per attendee. Average air travel-related carbon cost per attendee for different host cities ranged from 0.479 (London) to 0.919 (Vancouver) tonnes, with Ontario and Quebec sites averaging 0.518, Charlottetown 0.654 and Edmonton 0.756 tonnes. Ground transportation scores differed by city from Montreal (3/3 with public transit, formal transportation share and parking fees to dissuade driving) to London (0/3), with more favorable public transit options in larger cities. Venues differed when divided by hotel with meeting facilities (H) vs standalone conference center (CC), with CC outranking H for clearly posted sustainability plans (1.6 vs 1.2/2; 2=venue-specific, 1=company chain policy, 0=no plan), green and sustainable community building plans (1.6 vs 1.2/2; 2=greening local communities, 1=company chain policy, 0=no plan) and green waste management policies (1.2 vs 0/2; 2=venue-specific, 1=company chain policy, 0=no plan). Walkable accommodation was equal and present for all venues, with attached accommodation for all but one CC (Montreal), which had immediately adjacent hotels available. Conclusion: As expected, the carbon cost of air transportation per attendee was lower in central provinces. Ground transportation from the airport was better in larger host cities. Standalone conference centres had more sustainable event support and locally focused policies regarding sustainability, environmentally friendly community building initiatives and waste management solutions, three major components of "greening" conferences. Based on the available resources across Canada, we recommend that the CPS considers these sustainability criteria in planning future events.